Association between subclinical hypothyroidism and coronary artery disease: Subclinical Hypothyroidism and Coronary Artery Disease - Yaman, Belma; Cerit, Levent; Günsel, Hatice Kemal; Günsel, Aziz; Usalp, Songül; Yüksek, Ümit; Gül, İlker and Cerit, Zeynep and Etikan, İlker and Korkmaz, Aşkın Ali and Duygu, Hamza (Progress in Nutrition, 2019)
Coronary artery disease (CAD) is a common health problem with high morbidity and mortality. In recent years overt hypothyroidism is shown as an independent risk factor of CAD. Thyroid hormones have more effects on the cardiovascular system, and both hypothyroidism and hyperthyroidism have harmful effects on the cardiovascular systemç Subclinical hypothyroidism (SCH) is a common clinical situation with 4-20% frequency. SCH is associated with endothelial dysfunction, coronary atherosclerosis, and cerebrovascular disease. SYNTAX score is the angiographic scoring system and is widely used to evaluate the severity and complexity of CAD. The aim of this study to evaluate the association between SCH and SYNTAX score. This study is a retrospective cohort of participants who undergo coronary angiography and resulted in coronary artery bypass graft surgery. Participants divided into two group according to their SYNTAX score as high SYNTAX score (SYNTAX ≥ 23) and low SYNTAX score (SYNTAX<23). There is no statistically significant difference between two groups regarding age, male, height, weight, smoking, hypertension, diabetes mellitus, hyperlipidemia, peripheral artery disease, total cholesterol, HDL-C, LDL-C, TG, free thyroxine (fT4), free triiodothyronine (fT3), thyroid stimulating hormone (TSH), and uric acid. Serum LDL, total cholesterol levels are significantly higher in the SCH group than non-SCH group (respectively; p=0.029, p=0.024). There is a positive correlation between SCH and age, SCH prevalence increase with older age (p=0.017). Patients were divided into two group according to their TSH levels as SCH (fT3 and fT4 normal, TSH≥4). We used the SYNTAX score to evaluate the severity of CAD severity. However, there is no significant difference. Further studies are needed to evaluate the association between SCH and CAD.